Pengaruh Bermain Alat Musik Terhadap Kecerdasan Interpersonal Pada Anak Kelompok B Di Tk Aisyiyah Gonilan, Kartasura, Sukoharjo Tahun Ajaran 2016/2017 - Ayu Oktaviani, Dewi; , Surtikanti,SH,M.Pd (2017)
The purpose of this study was to determine the effect of the interpersonal playing a musical instrumentin group B children in kindergarten Aisyiyah Gonilan Kartasura Sukoharjo Academic Year 2016/2017. This research method is quantitative method, using a type of experimental research study design with pre-experimental design. Pre-experimental research design to form one group pretest-posttest design. This research was conducted in kindergarten Aisyiyah Gonilan Kartasura Sukoharjo. Subjects in this study were a group B kindergartenAisyiyah Gonilan with the number of 18 children. Data collection techniques in this research was conducted through observation, namely participant observation. Data analysis techniques in this study using ttest with SPSS 16.0 for Windows. The results of data analysis using ttest obtained thitung - 13.777 ≤ ttabel 1.740 then Ho rejected and Ha accepted which means there is the influence of playing a musical instrument to the interpersonal intelligence of children. Keywords: Playing a musical instrument, interpersonal intelligence